Rhodium(III)-catalyzed annulation of 2-arylimidazo[1, 2-a]pyridines and alkynes via direct double C–H activation. Issue 42 (21st October 2015) - Wang, Wei; Niu, Jun-Long; Liu, Wen-Bo; Shi, Tan-Hao; Hao, Xin-Qi; Song, Mao-Ping
Abstract: A series of naphtho[1′, 2′:4, 5]imidazo[1, 2- a ]pyridines were synthesized smoothly from 2-arylimidazo[1, 2- a ]pyridines and alkynes involving rhodium(III)-catalyzed C–H bond functionalization. The process selected Co(OAc)2 ·4H2 O as the co-catalyst for the first time and minimized the reaction time to 2 h under air atmosphere. Some products exhibited deep blue luminescence properties. Graphical abstract: